Integrated Planar Transformer for High-Voltage-Ratio LLC DCX With High Current and Ultra-Low Voltage Output - Kangping Wang; Yuhang Ning; Hongchang Li; Xu Yang (IEEE Open Journal of Power Electronics)
The 48 V voltage regulation modules (VRM) for microprocessors feature a high voltage transformation ratio, large current, and ultra-low voltage output. The solutions based on high-turns-ratio transformers are the most popular ones. However, these transformers often suffer from significant winding loss and large size issues, which are the main bottlenecks in improving efficiency and power density. This paper proposed a highly integrated planar transformer suitable for high-voltage-ratio VRMs with high current and ultra-low voltage output. The transformer integrates with the SRs and output capacitors and has a 1/10 turn on the secondary side, which can effectively reduce winding loss and improve power density. The winding length is determined by the size of the SRs and the output capacitors, resulting in a quite different design and optimization process from traditional transformers. The constraints of the transformer structure are analyzed and a flexible and compact structure is achieved on a 6-layer PCB. Based on the proposed transformer, a 40 V--1 V/200 A, 1 MHz LLC DCX is built. Experimental results show that the LLC DCX achieves a peak efficiency of 97% and a power density of 1394 W/in3, surpassing the state-of-the-art transformer-based solutions.